An Intimate Economy : Enslaved Women, Work, and America's Domestic Slave Trade - Finley, Alexandra J. (Book collections on Project MUSE., 2020)
"In the current boisterous debate over the relationship between slavery and capitalism, one subject has been conspicuously absent: women, both enslaved and free. This project places women's labor at the center of the antebellum slave trade, focusing particularly on slave traders' ability to profit from enslaved women's domestic, reproductive, and sexual labor. Alexandra J. Finley shows how women often performed the foundational labor necessary to the functioning of the slave trade, and thus to the spread of slavery to the Lower South, the expansion of cotton production, and the profits accompanying both of these markets. She makes this argument through five case studies, each of which highlights a particular woman or group of women who labored in the slave market. Some of these women performed domestic labor for slave traders, sewing outfits for enslaved people about to be sold, cooking meals for traders traveling to slave markets in New Orleans, or operating boarding houses where traders lodged. Many also performed reproductive labor, raising slave traders' children, giving birth to the future enslaved workforce, or practicing midwifery. Or they were chosen as concubines, or "fancy girls." Such women exemplify the importance of female labor to slave trading, performing domestic, reproductive, and sexual labor all at once for the man who enslaved them. In bringing a gendered perspective to the economic history of slavery, which is currently missing from the conversation, Finley demonstrates that women's labor was not "natural" or incidental to economic development, but a product of specific discourses about the biological roots of gender and race"--